Asymmetric diosmium sawhorse complexes. Issue 5 (9th April 2019) - Wilson, Kylie M.; Swartout, John W.; Touchton, Henry A.; Lambert, Erica N.; Johnstone, James E.; Archambeau, Ashley K.; Marolf, David M.; Mikeska, Emily R.; Lynch, Vincent M.; Nesterov, Vladimir N.; Reinheimer, Eric W.; Powell, Gregory L.; et al.
Abstract : The crystal structures of eight diosmium(I) carbonyl sawhorse complexes are reported, two with two axial CO ligands, two with one axial CO ligand and one axial phosphane ligand, and four with two axial phosphane ligands. One of the latter complexes also has two different bridging carboxylate groups and is the first example of a sawhorse complex with mixed carboxylate ligands. Abstract : Three asymmetric diosmium(I) carbonyl sawhorse complexes have been prepared by microwave heating. One of these complexes is of the type Os2 (μ‐O2 C R )(μ‐O2 C R ′)(CO)4 L 2, with two different bridging carboxylate ligands, while the other two complexes are of the type Os2 (μ‐O2 C R )2 (CO)5 L, with one axial CO ligand and one axial phosphane ligand. The mixed carboxylate complex Os2 (μ‐acetate)(μ‐propionate)(CO)4 [P( p ‐tolyl)3 ]2, (1 ), was prepared by heating Os3 (CO)12 with a mixture of acetic and propionic acids, isolating Os2 (μ‐acetate)(μ‐propionate)(CO)6, and then replacing two CO ligands with two phosphane ligands. This is the first example of an Os2 sawhorse complex with two different carboxylate bridges. The syntheses of Os2 (μ‐acetate)2 (CO)5 [P( p ‐tolyl)3 ], (3 ), and Os2 (μ‐propionate)2 (CO)5 [P( p ‐tolyl)3 ], (6 ), involved the reaction of Os3 (CO)12 with the appropriate carboxylic acid to initially produce Os2 (μ‐carboxylate)2 (CO)6, followed by treatment with refluxing tetrahydrofuran (THF) to form Os2 (μ‐carboxylate)2 (CO)5 (THF), and finally addition of tri‐ p ‐tolylphosphane to replace the THF ligand with the P( p ‐tolyl)3 ligand. Neutral complexes of the type Os2 (μ‐O2 C R )2 (CO)5 L had not previously been subjected to X‐ray crystallographic analysis. The more symmetrical disubstituted complexes, i.e. Os2 (μ‐formate)2 (CO)4 [P( p ‐tolyl)3 ]2, (8 ), Os2 (μ‐acetate)2 (CO)4 [P( p ‐tolyl)3 ]2, (4 ), and Os2 (μ‐propionate)2 (CO)4 [P( p ‐tolyl)3 ]2, (7 ), as well as the previously reported symmetrical unsubstituted complexes Os2 (μ‐acetate)2 (CO)6, (2 ), and Os2 (μ‐propionate)2 (CO)6, (5 ), were also prepared in order to examine the influence of axial ligand substitution on the Os—Os bond distance in these sawhorse molecules. Eight crystal structures have been determined and studied, namely μ‐acetato‐1κ O :2κ O ′‐μ‐propanoato‐1κ O :2κ O ′‐bis[tris(4‐methylphenyl)phosphane]‐1κ P, 2κ P ′‐bis(dicarbonylosmium)( Os — Os ) dichloromethane monosolvate, [Os2 (C2 H3 O2 )(C3 H5 O2 )(C21 H21 P)2 (CO)4 ]·CH2 Cl2, (1 ), bis(μ‐acetato‐1κ O :2κ O ′)bis(tricarbonylosmium)( Os — Os ), [Os2 (C2 H3 O2 )2 (CO)6 ], (2 ) (redetermined structure), bis(μ‐acetato‐1κ O :2κ O ′)pentacarbonyl‐1κ 2 C, 2κ 3 C ‐[tris(4‐methylphenyl)phosphane‐1κ P ]diosmium( Os — Os ), [Os2 (C2 H3 O2 )2 (C21 H21 P)(CO)5 ], (3 ), bis(μ‐acetato‐1κ O :2κ O ′)bis[tris(4‐methylphenyl)phosphane]‐1κ P, 2κ P ‐bis(dicarbonylosmium)( Os — Os ) p ‐xylene sesquisolvate, [Os2 (C2 H3 O2 )2 (C21 H21 P)2 (CO)4 ]·1.5C8 H10, (4 ), bis(μ‐propanoato‐1κ O :2κ O ′)bis(tricarbonylosmium)( Os — Os ), [Os2 (C3 H5 O2 )2 (CO)6 ], (5 ), pentacarbonyl‐1κ 2 C, 2κ 3 C ‐bis(μ‐propanoato‐1κ O :2κ O ′)[tris(4‐methylphenyl)phosphane‐1κ P ]diosmium( Os — Os ), [Os2 (C3 H5 O2 )2 (C21 H21 P)(CO)5 ], (6 ), bis(μ‐propanoato‐1κ O :2κ O ′)bis[tris(4‐methylphenyl)phosphane]‐1κ P, 2κ P ‐bis(dicarbonylosmium)( Os — Os ) dichloromethane monosolvate, [Os2 (C3 H5 O2 )2 (C21 H21 P)2 (CO)4 ]·CH2 Cl2, (7 ), and bis(μ‐formato‐1κ O :2κ O ′)bis[tris(4‐methylphenyl)phosphane]‐1κ P, 2κ P ‐bis(dicarbonylosmium)( Os — Os ), [Os2 (CHO2 )2 (C21 H21 P)2 (CO)4 ], (8 ).